PENGARUH FRAUD PENTAGON TERHADAP PERILAKU KECURANGAN AKADEMIK - Alfian, Nurull; Rahayu, Runik Puji (JURNAL AKUNTANSI DAN INVESTASI, 2021)
The purpose of this study was to determine the effect of the fraud pentagon on academic fraud behavior. Collecting data in this study was carried out with a quantitative type of research by distributing questionnaires to 100 (one hundred) students. The data analysis method used is using multiple linear regression analysis. The results showed that the fraud pentagon had a positive and significant effect on academic fraud behavior. Partially there is a positive and significant effect of pressure on academic cheating behavior, there is an insignificant effect of opportunity on academic cheating behavior, there is an insignificant effect of rationalization on academic cheating behavior, there is a positive and significant effect on the ability of academic cheating behavior and there is positive and significant influence of ethics on academic deficiency behavior.